Feature Papers in Electronic Materials Section - Roccaforte, Fabrizio (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book entitled "Feature Papers in Electronic Materials Section" is a collection of selected papers recently published on the journal Materials, focusing on the latest advances in electronic materials and devices in different fields (e.g., power- and high-frequency electronics, optoelectronic devices, detectors, etc.). In the first part of the book, many articles are dedicated to wide band gap semiconductors (e.g., SiC, GaN, Ga2O3, diamond), focusing on the current relevant materials and devices technology issues. The second part of the book is a miscellaneous of other electronics materials for various applications, including two-dimensional materials for optoelectronic and high-frequency devices. Finally, some recent advances in materials and flexible sensors for bioelectronics and medical applications are presented at the end of the book.